2010
DOI: 10.1227/01.neu.0000369517.21018.f2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Painful Seroma and Edema After the Use of Recombinant Human Bone Morphogenetic Protein-2 in Posterolateral Lumbar Spine Fusions

Abstract: There seems to be an increased incidence of formation of sterile seroma and painful edema in the lumbar region after posterolateral fusion with rhBMP-2. This report, along with other series highlighting the potential complications of bone morphogenetic proteins, suggests that more caution should be used when these compounds are used. Further studies are required to better define the risks and benefits of using bone morphogenetic proteins for spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 31 publications
0
76
1
Order By: Relevance
“…Thereafter, the ABBM bone grafting materials were implanted into 3mm critical size bone defects and investigated for 2 important parameters: 1) for their ability to regenerate appreciable new bone formation and 2) to investigate the immune response of ABBM which incorporate a natural atelocollagen protein within its scaffold [24][25][26]. It was first observed that after a healing period of 4 weeks, appreciable new bone formation took place demonstrating the grafts ability to regenerate new bone in a short period of time [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the ABBM bone grafting materials were implanted into 3mm critical size bone defects and investigated for 2 important parameters: 1) for their ability to regenerate appreciable new bone formation and 2) to investigate the immune response of ABBM which incorporate a natural atelocollagen protein within its scaffold [24][25][26]. It was first observed that after a healing period of 4 weeks, appreciable new bone formation took place demonstrating the grafts ability to regenerate new bone in a short period of time [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attempts have been made to attribute the formation of spinal seromas to the use of rhBMP-2, 1,3,4,[13][14][15] which is a recombinant human protein that has been used off label to promote bone arthrodesis in patients undergoing laminectomy and spinal fusion. It is believed to act through cellular, nuclear, and cytokine signaling to induce osteoblast differentiation and thus facilitate new bone growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several reports demonstrating an association between sterile postsurgical seroma formation and the use of rhBMP-2. 1,3,4,[12][13][14] Traditionally it is believed that these sterile seromas form as a result of trauma-induced inflammatory mediators that cause increased tissue capillary permeability in excess of local lymphatic drainage capacity. Surgical drainage of the fluid collection is often required, particularly in cases of neurological deterioration, and early detection is critical to prevent sequelae from cord compression.…”
mentioning
confidence: 99%
“…43 Garrett et al reported on the formation of painful postoperative seromas following the use of rhBMP-2 during posterolateral fusions. 23 Finally, Carragee et al identified a higher incidence of retrograde ejaculation in patients receiving rhBMP-2 during ALIF procedures.…”
Section: Singh Et Al 2006 IIImentioning
confidence: 99%